2017
DOI: 10.1111/bph.13846
|View full text |Cite|
|
Sign up to set email alerts
|

ELAC (3,12‐di‐O‐acetyl‐8‐O‐tigloilingol), a plant‐derived lathyrane diterpene, induces subventricular zone neural progenitor cell proliferation through PKCβ activation

Abstract: We propose lathyranes like ELAC as new drug candidates to modulate adult neurogenesis through PKC activation. Functional and structural comparisons between ELAC and phorboids are included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 65 publications
2
68
1
Order By: Relevance
“…We have studied in here the neurogenic effect of a small molecule, the diterpene with lathyrane skeleton EOF2. Unlike other lathyranes, EOF2 does not promote proliferation of NPC 22 . However, we have demonstrated that it specifically facilitates novel PKC-mediated NRG1 release, without affecting TGFα release.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…We have studied in here the neurogenic effect of a small molecule, the diterpene with lathyrane skeleton EOF2. Unlike other lathyranes, EOF2 does not promote proliferation of NPC 22 . However, we have demonstrated that it specifically facilitates novel PKC-mediated NRG1 release, without affecting TGFα release.…”
Section: Discussionmentioning
confidence: 79%
“…The lathyrane EOF2 (CAS number 2230806-06-9) was previously described by our group as a diterpene with no effect on NPC proliferation 22 . Since other diterpenes induced proliferation of NPC 24 via classical PKC activation 23 , we analyzed its capacity to activate PKC and to facilitate the generation of neurospheres.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations